Bispecific Antibody Armed Metabolically Enhanced Headless CAR T Cells - Thakur, Archana; Scholler, John; Kubicka, Ewa; Bliemeister, Edwin T.; Schalk, Dana L.; June, Carl H.; Lum, Lawrence G. (Frontiers in Immunology, 2021)
Adoptive T cell therapies for solid tumors is challenging. To address the inefficiency of T cells in the tumor microenvironment (TME), metabolically enhanced co-activated-T cells were produced by transducing intracellular co-stimulatory (41BB, ICOS or ICOS-27 and CD3ζ T cell receptor signaling domains followed by arming with bispecific antibodies (BiAbs) to produce armed “Bionic T cells” (BTC). The goal was to improve effector functions of BTC and enhance survival in the hypoxic TME. Various BTC armed with BiAb directed at CD3ε and various tumor associated antigens were tested for: 1) specific cytotoxicity against solid tumors targets; 2) repeated and dual sequential cytotoxicity; 3) survival and cytotoxicity in a hypoxia; and 4) cytokine secretion. The 41BBζ transduced BTC (BTC41BBζ armed with HER2 BiAb (HER2 BTC41BBζ or armed with EGFR BiAb (EGFR BTC41BBζ killed multiple tumor lines at effector to target ratio (E:T) of 2:1 or 1:1 significantly better than control T cells and secreted Th1 cytokines/chemokines upon tumor engagement. HER2 BTC serially killed tumor targets up to 14 days. Sequential targeting of EGFR or HER2 positive tumors with HER2 BTC41BBζ followed by EGFR BTC41BBζ showed significantly increased cytotoxicity compared single antigen targeting and continue to kill under hypoxic conditions. In summary, metabolically enhanced bionic T cells are effective serial killers of tumor targets, secrete cytokines and chemokines, and continue to kill under hypoxic conditions.